2016
DOI: 10.1001/jamapediatrics.2016.0269
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Racial Disparities in Child Asthma Readmission Using a Causal Inference Approach

Abstract: IMPORTANCE Childhood asthma is characterized by disparities in the experience of morbidity, including the risk for readmission to the hospital after an initial hospitalization. African American children have been shown to have more than 2 times the hazard of readmission when compared with their white counterparts.OBJECTIVE To explain why African American children are at greater risk for asthma-related readmissions than white children. DESIGN, SETTING, AND PARTICIPANTSThis study was completed as part of the Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 38 publications
0
85
0
Order By: Relevance
“…This finding is consistent with our previous work assessing relationships between index hospitalization and asthma-related rehospitalization. 27,36 Moreover, bivariate analyses suggest that black children are more likely than white ones to return for asthma-related revisits multiple times. Although black children were more likely to have multiple asthma-related revisits than white children, this does not appear to be related to overuse or misuse of the emergency setting (ie, children presenting when not ill).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our previous work assessing relationships between index hospitalization and asthma-related rehospitalization. 27,36 Moreover, bivariate analyses suggest that black children are more likely than white ones to return for asthma-related revisits multiple times. Although black children were more likely to have multiple asthma-related revisits than white children, this does not appear to be related to overuse or misuse of the emergency setting (ie, children presenting when not ill).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in the literature of the association between maternal smoking during pregnancy and risk of hospitalization in childhood 35,36 . In this study, children of mothers that smoked showed higher hospitalization rates than children born to mothers that did not smoke during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Asthma-related morbidity disproportionately affects racial minorities and the socioeconomically disadvantaged. (1–3) Marked disparities exist across regions with considerable neighborhood-to-neighborhood variability. (4) At the population level, areas with high rates of poverty, substandard housing, and crime have high rates of asthma morbidity.…”
mentioning
confidence: 99%
“…(59) At the patient level, influential factors may include socioeconomic status, culture, ethnicity, health beliefs, and gene-environment interactions. (3, 5, 1012) Factors related to these social determinants of health (SDH) play an undeniable role at both levels. (5)…”
mentioning
confidence: 99%